Pemanfaatan Ecobrick Menjadi Pojok Ekoliterasi Sebagai Upaya Menanggulangi Darurat Sampah Selama Pandemi Covid-19 Di Sekolah Dasar - Aziz , Al; Erlianda, Meyke; Agustina, Putri Ayuni; Mubarok, Irfan; Aryanto, Sani (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Bekasi is one of the cities that encourages all elements of society to be involved to overcome waste. Community Service that has been carried out is a concrete effort in providing preventive solutions through the use of ecobricks as an Pojok Ekoliterasi. The target of this service were 109 students and 11 teachers at SDN Kayuringin Jaya VI who are expected to represent elementary schools in Bekasi City. The method used in carrying out this service uses the scaffolding method, which is a method by providing structured assistance based on the difficulties experienced through extension activities, training, and science and technologqwwy assistance which are carried out in a blended. The objective target for four months proves that Pojok Ekoliterasi through the use of ecobricks for partners can be maximized, so that the program's objectives reaches 100%. this activity has the potential to become an excellent extracurricular program in elementary schools through intensive communication with partners. In addition, this program is considered potential to be continued with wider targets due to the existence of various dissemination through collaboration with the Bekasi City Government (MOU/016/V/2019/UBJ). Therefore, Pojok Ekoliterasi has the potential to be developed in elementary schools in the Bekasi City. in order to expand information related to the results of this service, we have also developed various supporting outputs that are more easily accessible to the public for free through guides, scientific articles, videos on YouTube, and the creation of intellectual property rights. The results of this study are expected to be a reference for other elementary schools in developing innovative programs to solve the problem of waste in Indonesia.